The Relationship between the Participation of the Bride and Groom in the Preconception Program with the Presence of Pure K1 - Farida Mamik Asih; Titik Suhartini; Iit Ermawati (Health and Technology Journal (HTechJ), 2023)
Reproductive health is the starting point for developing maternal and child health, which can be prepared early on, even before a woman becomes pregnant and a mother. Periconceptional health is part of the overall health between women and men during their reproductive years. This study aims to analyze the relationship between the participation of prospective brides and grooms in the preconception program with the presence of pure K1 in the work area of ​​the Kuripan Health Center, Probolinggo Regency. This quantitative research design uses a correlational design using a cross-sectional study approach with 30 respondents using an accidental sampling technique. Data collection included coding, editing, and tabulating, then analyzed manually and by computer with Uji Chi-Square. Based on data from 30 respondents, most of the bride and groom participated in the preconception program; 19 respondents (63.3%) with the presence of pure K1 18 respondents (60.0%) were present, while one respondent (3.3%) was absent. There was obtained p=0.000, so there is a relationship between the participation of the prospective bride and groom in the Preconception Program with the Presence of Pure K1 in the Work Area of ​​the Kuripan Health Center, Probolinggo Regency. It is hoped that preconception health care is a treatment that refers to biomedical, behavioral, and social prevention interventions that can increase the chances of having a healthy baby. To be able to create preconceptions, health can be done through preconception screening.